Severe Leptospirosis Features in the Spleen Indicate Cellular Immunosuppression Similar to That Found in Septic Shock - Duarte-Neto, Amaro Nunes; Croda, Julio; Pagliari, Carla; Soriano, Francisco Garcia; Nicodemo, Antonio Carlos; Duarte, Maria Irma Seixas (Frontiers in Immunology, 2019)
Objectives: to compare histological and immune features in the spleen in patients who died of pulmonary haemorrhage and shock caused by leptospirosis (11 cases), Gram-positive/-negative bacterial septic shock (10, autopsy) or controls (12, splenectomy). Methodology: histological features in the red pulp and white pulp were analyzed using archived samples by a semi quantitative score. Immunohistochemistry was used for the recognition of immune cell markers, cytokines, caspase-3 and Leptospira antigens. Results: the control group differed significantly from the leptospirosis and septic shock patients which demonstrate strong similarities: diffuse congestion in the red pulp with a moderate to intense infiltration of plasma cells and polymorphonuclear cells; follicles with marked atrophy; high density of CD20+ cells; low density of NK, TCD4+ and active caspase-3 positive cells and strong expression of IL-10; leptospirosis patients had higher S100 and TNF-α positive cells in the spleen than the other groups. Conclusion: the results suggest that an immunosuppressive state develops at the terminal stage of severe leptospirosis with pulmonary haemorrhage and shock similar to that of patients with septic shock, with a diffuse endothelial dysfunction in the spleen, splenitis and signs of disturbance in the innate and adaptive immunity in the spleen. The presence of leptospiral antigens in 73% of the spleens of the leptospirosis patients suggests the etiological agent contributes directly to the pathogenesis of the lesions. Our results support therapeutic approaches involving antibiotic and immunomodulatory treatments for leptospirosis patients and suggest that leptospirosis patients, which are usually young men with no co-morbidities, form a good group for studying sepsis and septic shock.